PENINGKATAN PRESTASI BELAJAR SISWA DENGAN MENERAPKAN METODE SOSIODRAMA - cahyono, hadi (Universitas Muhammadiyah Ponorogo, 2017)
The purpose of this research is to know the students’ achievement improvement of MTs Muhammadiyah 1 Ponorogo by using Sociodrama.This research outlines are the teaching process should be interesting and students’ achievement improved, but in fact, the teaching process result made the students bored so the achievement being low.The research method is descriptive qualitative and quantitative. Qualitative analysis used to analyze qualitative data. Qualitative data in form of sentence that give an information about students expression, the level of understanding, teaching learning process, students’ affective, enthusiasm, learning motivation, etc. The respondent is the eighth grade students B Class of MTs Muhammadiyah 1 Ponorogo. Techniques of collecting data are interview, observation, dan documentation. Quantitative methods used to analyze data.The result of this research showed that eighth grade students’ achievement improved by using sociodrama. It can be seen only two students who cannot pass the minimum standard qualification. Beside that, the student are being active than before in having teaching learning process.